2012
DOI: 10.4161/cl.19414
|View full text |Cite
|
Sign up to set email alerts
|

The SMS domain of Trs23p is responsible for the in vitro appearance of the TRAPP I complex inSaccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae transport protein particle (TRAPP) is a family of related multisubunit complexes required for endoplasmic reticulum-to-Golgi transport (TRAPP I), endosome-to-Golgi transport (TRAPP II) or cytosol to vacuole targeting (TRAPP III). To gain insight into the relationship between these complexes, we generated random and targeted mutations in the Trs23p core subunit. Remarkably, at physiological salt concentrations only two peaks (TRAPP I and a high molecular weight peak) are detected in wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 57 publications
(148 reference statements)
1
26
0
Order By: Relevance
“…When fused to GFP, the protein localizes to the plasma membrane and to small buds in dividing cells (Figure C). Previous studies have shown an accumulation of internal structures in trs85 Δ cells (Figure C). Similarly, we found internal, GFP‐Snc1p‐positive structures in trs20D46Y and trs20ts .…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…When fused to GFP, the protein localizes to the plasma membrane and to small buds in dividing cells (Figure C). Previous studies have shown an accumulation of internal structures in trs85 Δ cells (Figure C). Similarly, we found internal, GFP‐Snc1p‐positive structures in trs20D46Y and trs20ts .…”
Section: Resultssupporting
confidence: 52%
“…The subunit composition of TRAPP III differs from TRAPP I by just a single additional protein (Trs85p in TRAPP III), yet the molecular size of TRAPP III is much greater than that of TRAPP I (see Figures and ) and this is not due to oligomerization of Trs85p/TRAPP III (S.B. and M.S., unpublished observation).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, its mere existence in vivo has been questioned [57]. However, we argue that because TRAPP complexes tend to form dimers and aggregates [48,58], the low level of TRAPP I in cell lysates might not reflect the in vivo situation. Namely, while TRAPP I might exist in vivo, in cell lysates it associates with the larger TRAPP complexes.…”
Section: Trapp I or Core Trappmentioning
confidence: 86%
“…Subsequent phosphorylation of Sec23 by the Golgi‐localized kinase Hrr25 (casein kinase 1δ in humans) releases TRAPP I from the vesicle allowing fusion to proceed, a process that is conserved in humans . In spite of the elegant work performed on yeast TRAPP I, biochemical studies on the yeast Trs23 protein raised the possibility that TRAPP I is an in vitro artifact and may not exist in living cells, a notion that was recently supported by cell biological studies . This is consistent with the lack of identification of a mammalian TRAPP I equivalent and the inability to express recombinant human TRAPP I, while expression of recombinant yeast TRAPP I has been accomplished .…”
Section: The Trapp Family Of Multisubunit Tethering Factorsmentioning
confidence: 67%